Green capitalism or social and ecological justice? Analysing contested green hydrogen developments in Chile - Jakob Rammer (Südwind-Verlag, 2025)
he energy transition is not only topical in an European context, but has important ramification for the Global South. In his master's thesis, Jakob Rammer addresses this global dimension and provides a nuanced analysis of energy projects in Chile supported by European actors. Using the example of the emerging hydrogen sector in Chile, Jakob Rammer examines the complex interrelationships between global capitalist dynamics and local socio-ecological conflicts from a critical political-economic perspective. Building on a sophisticated theoretical framework that productively combines critical state theory, regulation theory, and political ecology, Mr. Rammer highlights the contradictions of green capitalist hegemony in Chile. Particularly noteworthy is the systematic analysis of the three competing political initiatives (export-oriented green capitalism, state-led energy transition and industrialization, social and ecological justice), which enables a nuanced understanding of the actor constellations at play. While the transition to renewable energies is important also in a Global South context, the study makes the important point that this must not lead to a renaissance of (post-)colonial extractivism at the expense of the local population and the environment. The thesis thus makes a significant contribution to the academic and policy discussions around the global energy transition by critically interrogating the economic and ecological repercussions of new investment projects in the Global South. – – Die Energiewende ist nicht nur in Europa ein aktuelles Thema, sondern hat auch weitreichende Konsequenzen für den Globalen Süden. In seiner Masterarbeit greift Jakob Rammer diese globale Dimension auf und analysiert differenziert Energieprojekte in Chile, die von europäischen Akteuren unterstützt werden. Am Beispiel des aufstrebenden Wasserstoffsektors in Chile untersucht er die komplexen Wechselwirkungen zwischen globaler kapitalistischer Dynamik und lokalen sozioökologischen Konflikten aus einer kritischen politökonomischen Perspektive. Auf der Grundlage eines differenzierten theoretischen Rahmens, der kritische Staatstheorie, Regulierungstheorie und politische Ökologie gewinnbringend miteinander verbindet, beleuchtet Rammer die Widersprüche der grünen kapitalistischen Hegemonie in Chile. Besonders hervorzuheben ist die systematische Analyse der drei konkurrierenden politischen Initiativen (exportorientierter grüner Kapitalismus, staatlich gelenkte Energiewende und Industrialisierung sowie soziale und ökologische Gerechtigkeit), die ein differenziertes Verständnis der beteiligten Akteurskonstellationen ermöglicht. Während der Übergang zu erneuerbaren Energien auch im Kontext des Globalen Südens wichtig ist, betont die Studie, dass dies nicht zu einer Renaissance des (post-)kolonialen Extraktivismus auf Kosten der lokalen Bevölkerung und der Umwelt führen darf. Die Arbeit leistet somit einen wichtigen Beitrag zu den akademischen und politischen Diskussionen über die globale Energiewende, indem sie die ökonomischen und ökologischen Auswirkungen neuer Investitionsprojekte im globalen Süden kritisch hinterfragt.
Keywords: 330